Cardio-Metabolic and Mental Health Outcomes Before and During the COVID-19 Pandemic in a Cohort of Women With Gestational Diabetes Mellitus in Switzerland - Quansah, Dan Yedu; Gilbert, Leah; Kosinski, Christophe; Le Dizès, Olivier; Horsch, Antje; Benhalima, Katrien; Cosson, Emmanuel; Puder, Jardena J. (Frontiers in Endocrinology, 2022)
Background: The COVID-19 pandemic has been associated with worsened metabolic and mental health in the general and perinatal population. The postpartum is a critical moment regarding these outcomes particularly in women with gestational diabetes mellitus (GDM). We investigated the cardio-metabolic and mental health outcomes before and during the pandemic in this population. Methods: This cohort included 418 women with GDM (n=180 exposed to the pandemic in 2020-2021 (E+) during their 6-8 weeks postpartum visit, n=238 attended a year before=non-exposed (E-)). Among the E+, a nested-subcohort of 120 women were exposed during pregnancy and postpartum. During the pandemic, follow-up was maintained in-person or via phone calls (35%) with a focus on healthy lifestyle behaviors. Obstetric, neonatal, cardio-metabolic and mental health outcomes were assessed during pregnancy and postpartum. Results: The pandemic was not associated with worsened weight, weight retention, glucose tolerance, metabolic syndrome, well-being or depression in the postpartum with the exception of a minimally increased HbA1c, diastolic blood pressure and lower emotional eating scores in E+ women (all p≤0.046). In the nested subcohort, E+ women had a slightly increased HbA1c at the first GDM visit and a higher need for glucose-lowering medication (both p≤0.014), but HbA1c at pregnancy end and other cardio-metabolic, mental health, obstetric and neonatal outcomes during pregnancy were similar. Conclusions: The pandemic was not associated with any clinically relevant worsening of cardio-metabolic, mental health, obstetrical and neonatal outcomes in our GDM cohort. This was possibly due to a continued hybrid follow-up, and the partial lockdown in Switzerland.